THE STRUGGLE OF THE MAIN CHARACTER TO OBTAIN FREEDOM IN COLSON WHITEHEADS THE UNDERGROUND RAILROAD - Shifa Fauziah; Shita Dewi Ratih P; Ade S. Natawiria (Universitas Pakuan, 2019)
Abstract This research, is an analysis on the main characters struggle to obtain her freedom based on The Underground Railroad, a novel by Colson Whitehead. The purpose of this research aims at the displaying modes of oppressions that the main character has to undergo as a dark-skinned slave secretly trying to find ways to escape. The data are analyzed with qualitative descriptive analysis method involving the intrinsic aspects and the theory of forms of oppression by Iris Young. In support of this study, library research technique is used for additional sources. The research results in the identification that the main character has to undergo fivefaces of oppression: exploitation, marginalization, powerlessness, cultural imperialsm, and violence. Eventually, it turns out that both internal and external factors have brought her a success in escaping from slavery and in winning her freedom. Keywords : black-skinned, freedom, oppression, slavery